Studying the recognition mechanism of TcaR and ssDNA using molecular dynamic simulations - Fan, Jing-rong (2020)
The transcription regulator teicoplanin-associate locus regulator (TcaR) plays a vital role in interfering with ssDNA replication and resisting ssDNA phage invasion. Although recent studies demonstrated that TcaR had strong interaction with ssDNA, the dynamics and interaction mechanism of dimeric TcaR bound to ssDNA have not been rationalized at the atomic level. In our study, MD simulations combined with MM-GB/SA calculations were employed to study recognition mechanism between TcaR and ssDNA. The results illuminate that electrostatic interaction is the main driving force for the binding process. We put forward that six anchoring residues (Arg70, Arg71, Ser188, Gln191, Arg221 and Arg222) play a vital role in stabilizing the ssDNA by forming strong hydrogen bond and salt bridge interactions. TcaR undergoes the asymmetric conformational changes at the wHTH domain upon binding to ssDNA. This may be attributed to the changing of electrostatic potential, enhanced contacts and salt bridge interaction. The present study provides new insights into the recognition mechanism of TcaR bound to ssDNA, which could contribute to understanding about the multiple TcaR functions in staphylococci enrich our understanding of MarR family.